2014
DOI: 10.3390/v6124856
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Species-Specific Interaction with the Basement Membrane-Resident Non-Heparan Sulfate Receptor

Abstract: Using a cell culture model where virus is bound to the extracellular matrix (ECM) prior to cell surface binding, we determined that human papillomavirus type 16 (HPV16) utilizes ECM resident laminin (LN) 332 as an attachment receptor for infectious entry. In presence of LN332, soluble heparin can function as ligand activator rather than competitive inhibitor of HPV16 infection. We also show that the ability to use LN332 binding as a productive attachment step for infectious entry is not conserved amongst HPV t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 76 publications
4
28
0
Order By: Relevance
“…However, the cleavage appeared to be inefficient unless the virus was preincubated with heparin. Since the interaction of HPV16 PsV with highly sulfated HS facilitates infection by induction of a conformational change in virions (19,70), it is likely that this conformational change exposed a protease consensus sequence of L1 that was at least partially obscured in the incoming HPV16 PsV.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cleavage appeared to be inefficient unless the virus was preincubated with heparin. Since the interaction of HPV16 PsV with highly sulfated HS facilitates infection by induction of a conformational change in virions (19,70), it is likely that this conformational change exposed a protease consensus sequence of L1 that was at least partially obscured in the incoming HPV16 PsV.…”
Section: Discussionmentioning
confidence: 99%
“…4E), did not completely abolish the binding of AGMA1 to the cells (leaving 50% of binding unaffected), suggesting that other surface receptors, as yet unidentified, may be able to interact with the polymer. Of note, beside HSPGs, other cell receptors have been identified that contribute to HPV infection, including ␣6␤4 integrin (36) and annexin A2 (37), and some reports even suggest the possibility that HPV infection occurs in a HSPG-independent manner (38,39). Interestingly, the levels of cell surface expression of HSPGs (40) and of heparinase (41) can vary during inflammation, which is normally triggered by viral infections, suggesting the possibility that, depending on the pathological setting, HSPGs or other (as yet unidentified) HPV receptors may contribute differently to HPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…HPV are epitheliotropic viruses whose replication cycle is strictly dependent on the terminal differentiation process of keratinocytes of the skin and mucosa (Doorbar et al, 2015). To achieve entry, HPV preferentially binds to components of the basement membrane, which separates the epidermal from the dermal tissue (Culp et al, 2006a;Selinka et al, 2007;Richards et al, 2014). Animal models have revealed that access to the basement membrane requires disruption of the epidermal architecture such as wounds, abrasions or microlesions (Roberts et al, 2007).…”
Section: Hpv Is Delivered Into the Nucleus In A Transport Vesiclementioning
confidence: 99%